Successful Percutaneous Coronary Intervention Using Intravascular Ultrasound-Guided Rewiring Technique in a Case of Spontaneous Coronary Artery Dissection Involving Left Main Bifurcation. (3rd July 2020) - Numasawa, Yohei; Yokokura, Souichi; Hitomi, Yasuhiro; Imaeda, Shohei; Tanaka, Makoto; Tabei, Ryota; Kodaira, Masaki
Abstract : We herein describe a 49-year-old woman without significant cardiovascular risk factors who was transferred to our hospital with sudden onset of chest pain. The patient was diagnosed with non-ST-elevation acute myocardial infarction, and coronary angiography revealed a dissection at the proximal site of the left anterior descending artery (LAD) extending from the left main trunk (LMT) suggestive of spontaneous coronary artery dissection (SCAD). Because coronary flow was impaired after contrast injection and the patient had chest pain with ST elevation, urgent percutaneous coronary intervention was performed. The first guide wire was initially introduced from the LMT to the distal LAD, but intravascular ultrasound (IVUS) imaging revealed that the guide wire had passed through the true lumen of the left coronary artery ostium, false lumen at the ostium of the left circumflex artery, and true lumen of the distal LAD. We then reinserted another guide wire using an IVUS-guided rewiring technique from the true lumen of the LMT to the distal LAD. Finally, a drug-eluting stent was deployed to cover the dissected segment, and final coronary angiography revealed acceptable results with a patent left circumflex artery. This case report highlights that physicians should consider SCAD among the differential diagnoses in patients presenting with acute coronary syndrome, particularly in young women. In the present case, IVUS played a pivotal role in not only detecting the arterial dissection but also correctly introducing the guide wire into the true lumen.